2016
DOI: 10.5897/ajb2015.15070
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antioxidant effects and antimicrobial activities of some spices essential oils on food pathogenic bacteria

Abstract: Thymus vulgaris, Cinnamomum zeylanicum and Ocimum gratissimum are spices widely used as aroma enhancers and food preservatives. This work assessed the chemical composition, antioxidant and antimicrobial effect of their essential oils on some food pathogenic bacteria, namely, Staphylococcus aureus, Citrobacter freundii, Enterobacter cloacae, Morganella morganii, Escherichia coli, Salmonella typhimurium, Proteus vulgaris and Shigella flexineri. After chemical analyses of the essential oils by gas chromatography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…For example, Boskovic et al (2015) showed that thymol, p-cymene, linalool, γ-terpinene, and 1,8-cineole were the most dominant compounds of thyme essential oil (50.48%, 24.79%, 4.69%, 4.14%, and 4.35% of the oil, respectively). Additionally, the results of other previous studies revealed that thymol was the most common components of T. vulgaris oil (Lee et al, 2005;Ferreira et al, 2016;Foe et al, 2016;Moghaddaszadeh-Ardebili, 2016;Mohammed et al, 2016;Szczepanik et al, 2012). In contrast, Quesada et al (2016) used a chemotype of TVE with low odor intensity that did not have any thymol and had a very low content of linalool with the major component of 1,8 cineole.…”
Section: Discussionmentioning
confidence: 85%
“…For example, Boskovic et al (2015) showed that thymol, p-cymene, linalool, γ-terpinene, and 1,8-cineole were the most dominant compounds of thyme essential oil (50.48%, 24.79%, 4.69%, 4.14%, and 4.35% of the oil, respectively). Additionally, the results of other previous studies revealed that thymol was the most common components of T. vulgaris oil (Lee et al, 2005;Ferreira et al, 2016;Foe et al, 2016;Moghaddaszadeh-Ardebili, 2016;Mohammed et al, 2016;Szczepanik et al, 2012). In contrast, Quesada et al (2016) used a chemotype of TVE with low odor intensity that did not have any thymol and had a very low content of linalool with the major component of 1,8 cineole.…”
Section: Discussionmentioning
confidence: 85%
“…The plant material, known as Thyme white, containing a slight prevalence of p‐cymene over thymol was applied in the studies by Kim et al (2019) and Shin et al (2019). A higher level of p‐cymene prevalence (45.90%) over thymol (23.72%) was demonstrated in the study by Foe et al (2016), who classified this chemotype as a p‐cymene. The prevalence of p‐cymene (32.18%) over thymol (19.38%) was found in the essential oil of two‐year‐old plants that were collected in December, while thymol dominated in essential oils of two‐ and five‐year‐old plants that were collected in June and July.…”
Section: Discussionmentioning
confidence: 85%
“…The plant material, known as Thyme white, containing a slight prevalence of p-cymene over thymol was applied in the studies by Kim et al (2019) and Shin et al (2019). A higher level of p-cymene prevalence (45.90%) over thymol (23.72%) was demonstrated in the study by Foe et al (2016), who classified this chemotype as a p-cymene.…”
Section: Discussionmentioning
confidence: 99%